The problem of resocialisation of criminals comitting sexual crimes in the light of Kazimierz Dąbrowski’s theory of positive disintegration - Kędrzyński, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
Kazimierz Dąbrowski’s theory of positive disintegration is a quite complex theoretical concept which can be characterized as a scientific model. Its analysis can provide us with an interesting look into extremely diverse topics, for example into a question of resocialisation of criminals committing sexual crimes. The aim of this article was the description of the presented theory and its potential usage in the practical issue of penalisation and resocialisation of criminals committing sexual crimes. Conclusions were drawn on both legal and political surfaces.